Users’ perceptions of algorithmic communicative agency in the United Arab Emirates: An exploratory study of the impact of recommendation and trending systems on digital public discourse - Alhooti, Noora; AlMazaedh, Ismaael Suleman (Research Journal in Advanced Humanities, 2026)
Digital platforms serve as crucial spaces for public communication today, influenced heavily by algorithmic recommendation systems that determine visibility and engagement. This study focuses on user perceptions of algorithmic communicative agency within the context of the United Arab Emirates, utilizing an exploratory survey approach with samples from general users and digital content creators. Rather than directly auditing algorithms, it emphasizes perceived influence, as users’ beliefs about algorithms often have a greater impact on their trust and engagement than their technical understanding. The survey assessed various dimensions, including perceived agency, diversity of exposure, polarization, and the credibility of algorithmically generated content. Results show that both user groups see platform algorithms as active agents affecting visibility and discourse. Increased perceptions of algorithmic agency correlate with reduced diversity of information, heightened polarization, and greater conformity in expression, alongside rising concerns about toxic interactions. The credibility associated with algorithmically promoted content is viewed ambivalently, revealing a complex relationship between perceived legitimacy and concerns about bias. Content creators, in particular, feel a stronger impact from algorithms regarding their visibility and reach. This research underscores the need for user-centered insights in discussions about platform regulation and digital literacy, laying groundwork for future expansive research on algorithmic influence in the Arab public sphere.